Empowering accounting students to enhance the self-determination skills demanded by the fourth industrial revolution - Karsten, I.; van der Merwe, M.; Steenekamp, K. (South African Journal of Higher Education, 2020)
This article proffers consideration of multiple factors by higher education institutions to address the complex challenge of preparing students for the changing world of work. We argue that student support should be holistic, offering academic as well as non-academic support and suggest an intervention where 21st Century skills are offered to students, within the intricate context of the fourth industrial revolution (4IR) with its multiple challenges and opportunities. We further argue that an integration of self-determination principles within such an intervention embedded in Self-Determination Theory (SDT) be considered within student education and support. Student integration research (Tinto 2003) underpinned a proposed strategy to answer important questions regarding student support, namely: “What is needed and when?” Complementary to this, the theory of Self-Determination offered a solid conceptual framework where 21st Century skills could practically be implemented and as such answer the question: “How can students be empowered?” The research followed a design-based process, positioned in the pragmatic paradigm. The methodology of Design Based Research (DBR) is known for creating knowledge to solve real-world problems in a practical manner. The study was conducted with students from a residential South African university and reports mainly on qualitative data from three consecutive cohorts of first-year Accounting students. This study proposes action to empower students with 21st Century skills through holistic support, embedded in the Self-Determination Theory, within the context of the 4IR.